Disappearing seasonality in birthweight - Sohn, Kitae (John Wiley & Sons, Inc., 2016)
© 2016 Wiley Periodicals, Inc.Objectives: We estimated seasonality in birthweight over time and assessed how seasonality changed. Methods: We analyzed all full-term singletons (N = 8,268,693) born in South Korea in 1997–2014. We first pooled all years and regressed birthweight on birth season while flexibly controlling for a large set of covariates. We then repeated the analysis by birth year and charted the trends in seasonality in birthweight. Results: When we pooled all years, babies born in winter were the heaviest, while those born in summer the lightest; the difference in birthweight was about 11 g. When we analyzed the data by birth year, however, seasonality almost disappeared by the end of the period. Conclusions: Whatever causes the seasonality has lost its influence in Korea. Replication studies can determine whether other countries exhibit the same patterns. Am. J. Hum. Biol. 28:767–773, 2016. © 2016Wiley Periodicals, Inc.